Percutaneous liver venous deprivation: outcomes in heavily pretreated metastatic colorectal cancer patients. Issue 3 (March 2022) - Ghosn, Mario; Kingham, T. Peter; Ridouani, Fourat; Santos, Ernesto; Yarmohammadi, Hooman; Boas, Franz E.; Covey, Anne M.; Brody, Lynn A.; Jarnagin, William R.; D'Angelica, Michael I.; Kemeny, Nancy E.; Solomon, Stephen B.; et al.
Abstract: Background: To evaluate liver venous deprivation (LVD) outcomes in patients with colorectal liver metastasis (CRLM) heavily pretreated with systemic and hepatic arterial infusion pump (HAIP) chemotherapies that had an anticipated insufficient future liver remnant (FLR) hypertrophy after portal vein embolization (PVE). Methods: PVE was performed with liquid embolics using a transsplenic or ipsilateral transhepatic approach. Simultaneously and via a trans-jugular approach, the right hepatic vein was embolized with vascular plugs. Liver volumetry was assessed on computed tomography before and 3–6 weeks after LVD. Results: Twelve consecutive CRLM patients that underwent LVD before right hepatectomy or trisectionectomy were included, all previously treated with systemic chemotherapy for a mean of 11.9 months. Six patients had additional HAIP. After embolization, FLR ratio increased from 28.7% ± 5.9 to 42.2% ± 9.0 ( P < 0.01). Mean kinetic growth rate (KGR) was 3.56%/week ± 2.3, with a degree of hypertrophy (DH) of 13.8% ± 7.1. In the HAIP subgroup, mean KGR and DH were respectively 3.58%/week ± 2.8 and 14.3% ± 8.7. No severe complications occurred. Ten patients reached surgery after 39 days ± 7.5. Conclusion: In heavily pretreated patients, LVD safely stimulated a rapid and effective FLR hypertrophy, with a resultant high rate of resection.